Utilization of Milkfish for Milkfish Dumplings for The Community of Serang - Dabella Yunia; Muhammad Galih Ferginanto (EQUATOR SINAR AKADEMIA, 2021)
This community aims to increase the creativity of the community which provides value added economic for milkfish. This activity was carried out by inviting the community to give presentations on entrepreneurship, then providing training to make milkfish dumplings. This is a business strategy that simultaneously raises local resources.